ANALISIS PEUBAH KONSUMSI PANGAN DAN SOSIAL EKONOMI UNTUK MENENTUKAN INDIKATOR KELAPARAN - bakar, abu (Universitas Djuanda Bogor, 2011)
Aim of the study was to analyze food consumption and socio-economic parameters in order for determine starvation indicators. The study was designed in a cross sectional method and samples collected in gradual cluster. First cluster consisted of four sub districts with eight selected-villages and as many as 233 samples were withdrawn from the eight villages for analyzing in discrimination method. If rice were used as starvation indicator, 48.5% of samples suffered starvation. The study resulted that 85% of the samples ate twice daily while 15% of the samples ate three times in a day. According to frequency of food consumption as starvation indicator, the samples did not suffer from starvation. In addition, the study showed that 45.8% samples of city areas which the member more than four people suffered starvation and so did the 68.1% samples lived in villages which the member more than four people. Moreover, 15% of husband which bachelor degree holders lived in city areas and 1.8% of husband which bachelor degree holders lived in villages did not suffer from starvation. As many as 45% of heads of families whose work as government employees at city areas and 2.7% of heads of families whose work as government employees at villages did not suffered from starvation. Based on food expenses criteria used as a starvation indicator, 32.5% samples lived at city areas and 83.2% samples lived at villages were suffer from starvation. The study showed that high sensitivity at either cities or villages occurred on bachelor degree holders and government employeeÃ¢â¬â¢s criteria, and contrary, the high specificity at either cities or villages occurred on government employeeÃ¢â¬â¢s criteria when food expenses criteria used as a gold standard